LAYER COMPOSITING EFFECT IN THE PROPERTIES OF DIFFERENT WOOD PANELS TYPE (FLAKEBOARD, OSB AND OSL) - Napoli, Lygia Maria; Bednarczuk, Ezaquel; Natalli, Luiz Henrique; Hillig, Everton; Ferro, Fabiane Salles (Floresta, 2023)
The objective was to evaluate the effect of layered composition on the properties of panels manufactured using Pinus taeda wood flakes particles, phenol-formaldehyde resin, a nominal density of 0.65 g/cm³ and seven types of the panel layers compositions. The tests were carried out according to the series of European standards for wood-based panels. The results showed that the P6 panel type (20/60S/20 composition), with a randomly distributed central layer, exhibited greater dimensional stability. The panel P4 (30/40/30) showed better results for static bending properties in the parallel direction, whereas the P2 panel (10/80/10) did so in the perpendicular direction. The P3 Panel (20/60/20), showed a better balance of bending properties in both directions. The OSL displayed physical properties similar to OSB and better results for MOR and MOE results in the parallel direction, regardless of the layer composition. The quadratic regression based on the proportion of the parallel external layer enabled the estimation of parallel and perpendicular MOR and MOE losses and gains.